Delirium in Patients with SARS‐CoV‐2 Infection: A Multicenter Study. Issue 2 (8th December 2020) - Rebora, Paola; Rozzini, Renzo; Bianchetti, Angelo; Blangiardo, Paolo; Marchegiani, Alice; Piazzoli, Andrea; Mazzeo, Francesca; Cesaroni, Giulia; Chizzoli, Anita; Guerini, Fabio; Bonfanti, Paolo; Morandi, Alessandro; et al.
Abstract : Objectives: The aims of this study are to report the prevalence of delirium on admission to the unit in patients hospitalized with SARS‐CoV‐2 infection, to identify the factors associated with delirium, and to evaluate the association between delirium and in‐hospital mortality. Design: Multicenter observational cohort study. Settings: Acute medical units in four Italian hospitals. Participants: A total of 516 patients (median age 78 years) admitted to the participating centers with SARS‐CoV‐2 infection from February 22 to May 17, 2020. Measurements: Comprehensive medical assessment with detailed history, physical examinations, functional status, laboratory and imaging procedures. On admission, delirium was determined by the Diagnostic and Statistical Manual of Mental Disorders (5th edition) criteria, 4AT, m‐Richmond Agitation Sedation Scale, or clinical impression depending on the site. The primary outcomes were delirium rates and in‐hospital mortality. Results: Overall, 73 (14.1%, 95% confidence interval (CI) = 11.0–17.3%) patients presented delirium on admission. Factors significantly associated with delirium were dementia (odds ratio, OR = 4.66, 95% CI = 2.03–10.69), the number of chronic diseases (OR = 1.20, 95% CI = 1.03; 1.40), and chest X‐ray or CT opacity (OR = 3.29, 95% CI = 1.12–9.64 and 3.35, 95% CI = 1.07–10.47, for multiple or bilateral opacities and single opacity vs no opacity, respectively). There were 148 (33.4%) in‐hospital deaths in the no‐delirium group and 43 (58.9%) in the delirium group ( P ‐value assessed using the Gray test <.001). As assessed by a multivariable Cox model, patients with delirium on admission showed an almost twofold increased hazard ratio for in‐hospital mortality with respect to patients without delirium (hazard ratio = 1.88, 95% CI = 1.25–2.83). Conclusion: Delirium is prevalent and associated with in‐hospital mortality among older patients hospitalized with SARS‐CoV‐2 infection.